Human CD36 overexpression in renal tubules accelerates the progression of renal diseases in a mouse model of folic acid-induced acute kidney injury - Jong Hwan Jung; Jee Eun Choi; Ju Hung Song; Seon-Ho Ahn (The Korean Society of Nephrology, 2018)
Background : Acute kidney injury (AKI) is a risk factor for progression to chronic kidney disease, with even subclinical AKI episodes progressing to chronic kidney disease. Several risk factors such as preexisting kidney disease, hyperglycemia, and hypertension may aggravate renal disease after AKI. However, mechanisms underlying the progression of AKI are still unclear. This study identified the effect of human cluster of differentiation 36 (CD36) overexpression on the progression of folic acid-induced AKI. Methods : Pax8-rtTA/tetracycline response element-human CD36 transgenic mice were used to elucidate the effect of human CD36 overexpression in the proximal tubules on folic acid-induced AKI. Results : Results of histological analysis showed severely dilated tubules with casts and albuminuria in folic acid-treated transgenic mice overexpressing human CD36 compared with folic acid-treated wild-type mice. In addition, analysis of mRNA expression showed a significant increase in the collagen 3a1 gene in folic acid-treated transgenic mice overexpressing human CD 36 compared with folic acid-treated wild type mice. Conclusion : Human CD36-overexpressing transgenic mice showed severe pathological changes and albuminuria compared with wild-type mice. Moreover, mRNA expression of the collagen 3a1 gene increased in folic acid-treated transgenic mice. These results suggest that human CD36 overexpression is a risk factor of AKI and its progression to chronic kidney disease.